Response To Changes in Water Temperature Based on Operculum Movement in Nile Tilapia (Oreochromis niloticus) - Alyaminy, Ishmah Humaidatul Aminah Zaim; Sanuriza, Irna Il; Risfianty, Dwi Kartika; Jayadi, Irfan; Ihwan, Khaerul; Atika, Baiq Naili Dewi; Dewi, Irma Risvana; Harmayani, Ria; Syarifa, Faridatus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The objective of this study is to examine the physiological response of Oreochromis niloticus at different water temperatures using laboratory experimental methods (experimental research carried out under controlled conditions and allows for systematic and accurate measurements). The observation method uses descriptive analysis. Based on the results of the study, it can be concluded that when Oreochromis niloticus is in a water environment with low temperatures (140 C and 200C), the movement of the operculum will decrease. This is due to an increase in dissolved oxygen levels and cold-water temperatures will affect the metabolism of the fish body. Whereas when Oreochromis niloticus is in a water environment with high temperatures (320 C, and 380 C), operculum movement will increase. The increase in operculum movement is caused by a decrease in dissolved oxygen levels.